Epistemologi Penafsiran Esoterik Al-Qur’an: Diskursus Tafsir dan Takwil dalam Tradisi Sufistik - Trisna Yudistira; Moh. Anwar Syarifuddin (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2026)
Esoteric interpretation of the Qur’an has long occupied a significant place in the Islamic exegetical tradition, particularly within Sufi intellectual and spiritual circles. Existing studies on esoteric interpretation have largely focused on interpretive products and Sufi symbolism, while limited attention has been given to the epistemological foundations that distinguish tafsīr and taʾwīl as the conceptual basis of esoteric interpretation. This article aims to analyze the epistemological relationship between tafsīr, taʾwīl, and esoteric interpretation through a conceptual and philosophical-hermeneutical analysis of classical and contemporary literature. The findings reveal that, epistemologically, esoteric interpretation is more closely related to the concept of taʾwīl than to tafsīr in its formal sense. The narrowing of the meaning of tafsīr within the Islamic scholarly tradition has generated various criticisms of esoteric interpretation, as it is often regarded as failing to meet the standards of exegesis oriented toward authorial intent. In contrast, esoteric interpretation operates through the reader’s horizon, shaped by spiritual experience, intuition, and kashf, in order to uncover the symbolic meanings of the text. These findings suggest that the relationship between tafsīr and taʾwīl may be understood as a hermeneutical distinction between exegesis and eisegesis, while simultaneously affirming esoteric interpretation as a legitimate epistemological model within the tradition of Qur’anic studies.